Implementasi Algoritma Chaskey-12 Cipher untuk Mengamankan Data Sensor pada Komunikasi antara Node Sensor, Gateway dan Cloud - Fanny Aulia Rifki; Adhitya Bhawiyuga; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Data is one of the objects in a technology that is vulnerable to attacks on cryptographic aspects of confidentiality and integrity. Attacks on confidentiality and integrity aspects can be prevented by building a data security mechanism that implements cryptographic algorithms. However, not all technologies have data security mechanisms because the devices used have limited resources. So in this study, the authors build a data security mechanism on communication between sensor nodes, gateways, and the cloud using the Chaskey-12 cipher algorithm which is suitable for devices with limited resources. The author implements the Chaskey-12 cipher algorithm with CBC operating mode in the encryption and decryption process to ensure the confidentiality of sensor data. Meanwhile, to ensure the integrity of sensor data, the author implements the Chaskey-12 cipher algorithm in the process of tag formation and tag verification. Based on several test results in this study, it is known that the sensor, gateway, and cloud nodes successfully implement the Chaskey-12 cipher algorithm and carry out their functions in securing sensor data. The test vector test results show that the Chaskey-12 cipher algorithm in this study has been implemented according to the paper of the Chaskey-12 cipher algorithm creator. The performance test results show that node sensor, gateways, and cloud require a low average execution time with a high throughput value. The security test results show that the Chaskey-12 cipher algorithm implemented by the author succeeded in guaranteeing the confidentiality and integrity aspects of the sensor data security mechanism.